PEMANFAATAN LIMBAH KULIT PISANG KEPOK (Musa paradisiaca) TERHADAP PENURUNAN KADAR KOLESTEROL LDL PADA Rattus norvegicus YANG DIINDUKSI STREPTOZOTOCIN - Fityah Ufi Atiyah (FKU 15 UMY 589, 2015)
Diabetes mellitus is the fourth causes of non communicable diseases. Diabetes meillitus is caused by an altered insulin secretion, function or both. One of the risk factor of Coronary Heart Disease for patient with DM type 2 is dyslipidemia. Dyslipidemia is a lipid profile abnormality such as the increasing of total cholesterol level, trigliseride, LDL and the decreasing of HDL level. At DM condition, patients will encounter a lipid profile change such as hypercholesterolemia, hypertrigliseride, and the increasing of LDL level. The aim for this study was to see the effectivity of kepok banana peel waste product in order to decrease LDL-Cholesterol level on streptozocin inducted Rattus norvegicus. This study is an experimental research with pre and post test control design. Samples included for this research were 25 Rattus norvegicus. Data were analyzed with wilcoxon test, kruskall wallis, and mann withney test. The duration for this study was 21 days. LDL level data were taken twice during the research; before and after the experiment. Analysis result on Utilization of kepok banana peel waste product to decrease LDL-Cholesterol level on streptozocin inducted Rattus norvegicus shows result with p value=0,043 at the doses 400 mg/kgBB, 200 mg/kgBB and 100 mg/kgBB. Thus, it can be concluded that there is a significant difference between LDL level before and after experimen